Human Rights Education in Argentina. Notes on the process of incorporating human rights in educational contexts - Fernández, Mónica (2016)
This work makes a synthetic characterization of the various political and economic contexts for enabling the incorporation of human rights in various institutions of Argentina, through of informal educational to eventually form part of the curricula at all educational levels. The purpose is to visualize as was developed and which spheres of culture demanded the need to educate in and for human rights. Since one of the purposes of education is the need to educate the citizenship, this article aims to make visible that human rights are a way to exercise the citizenship and educational sphere is the context so that human rights are respected in the diverse cultural practices.